Integration of Digital Technology in Islamic Education: a Case Study of SMA Negeri 1 Wanasaba in 2023 - Nasri, Ulyan; Rahmatullah, Abdul Malik Salim (Al Hikmah: Journal of Education, 2024)
This research aims to explore the integration of digital technology into Islamic education at SMA Negeri 1 Wanasaba in 2023. The study outlines the rapid evolution of digital technology and its impact on teaching and learning methodologies within the context of Islamic education. SMA Negeri 1 Wanasaba was selected for its representativeness of secondary education institutions in the region. A qualitative research approach was employed, utilizing in-depth interviews and observations as data collection techniques. Participants included teachers and students actively engaged with digital technology in the Islamic education setting at the school. Data analysis was performed using an inductive approach, providing detailed qualitative insights from the interviews and observations. The research findings offer a thorough understanding of how digital technology influences Islamic education at SMA Negeri 1 Wanasaba, highlighting both the benefits and challenges of technology integration. The study suggests recommendations for curriculum development, teacher training, and managing technological resources in Islamic education environments. By examining the role of digital technology, this research aims to support SMA Negeri 1 Wanasaba and similar institutions in leveraging its advantages while addressing potential challenges. This study contributes to a contextual understanding of technology integration in secondary-level Islamic education.